Elucidation of motifs in ribosomal protein S9 that mediate its nucleolar localization and binding to NPM1/nucleophosmin. - Mikael S Lindström (Public Library of Science (PLoS), 2012)
Biogenesis of eukaryotic ribosomes occurs mainly in a specific subnuclear compartment, the nucleolus, and involves the coordinated assembly of ribosomal RNA and ribosomal proteins. Identification of amino acid sequences mediating nucleolar localization of ribosomal proteins may provide important clues to understand the early steps in ribosome biogenesis. Human ribosomal protein S9 (RPS9), known in prokaryotes as RPS4, plays a critical role in ribosome biogenesis and directly binds to ribosomal RNA. RPS9 is targeted to the nucleolus but the regions in the protein that determine its localization remains unknown. Cellular expression of RPS9 deletion mutants revealed that it has three regions capable of driving nuclear localization of a fused enhanced green fluorescent protein (EGFP). The first region was mapped to the RPS9 N-terminus while the second one was located in the proteins C-terminus. The central and third region in RPS9 also behaved as a strong nucleolar localization signal and was hence sufficient to cause accumulation of EGFP in the nucleolus. RPS9 was previously shown to interact with the abundant nucleolar chaperone NPM1 (nucleophosmin). Evaluating different RPS9 fragments for their ability to bind NPM1 indicated that there are two binding sites for NPM1 on RPS9. Enforced expression of NPM1 resulted in nucleolar accumulation of a predominantly nucleoplasmic RPS9 mutant. Moreover, it was found that expression of a subset of RPS9 deletion mutants resulted in altered nucleolar morphology as evidenced by changes in the localization patterns of NPM1, fibrillarin and the silver stained nucleolar organizer regions. In conclusion, RPS9 has three regions that each are competent for nuclear localization, but only the central region acted as a potent nucleolar localization signal. Interestingly, the RPS9 nucleolar localization signal is residing in a highly conserved domain corresponding to a ribosomal RNA binding site.